Ternary positive electrode material and preparation method thereof

CN117766715BActive Publication Date: 2026-11-03NANTONG RESHINE NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311783587.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2026-11-03
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

In existing technologies, imperfect coating processes lead to material loss in ternary cathode materials, resulting in a large discrepancy between the actual coating amount and the design value, which affects the performance improvement effect.

Method used

High-pressure spraying technology is used to mix a solvent and a first metal compound that is insoluble in the solvent with a second metal compound that is soluble in the solvent to form a uniformly dispersed solid-liquid mixture system, which is then coated onto the surface of a preheated substrate and dried and sintered at high temperature to form a stable coating layer.

Benefits of technology

It reduces the loss of coating material, narrows the gap between the actual coating amount and the design value, and improves the uniformity of the coating layer and the long-term cycle stability of the cathode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117766715B_ABST
    Figure CN117766715B_ABST
Patent Text Reader

Abstract

The application discloses a ternary positive electrode material and a preparation method thereof, and belongs to the technical field of lithium battery positive electrode materials. The preparation method comprises the following steps: firstly, mixing a solvent, a first metal compound insoluble in the solvent and a second metal compound soluble in the solvent according to a preset solid-liquid ratio, so as to form a uniformly dispersed solid-liquid mixed system; and secondly, wrapping the solid-liquid mixed system on the surface of a substrate preheated to a first temperature in a high-pressure spraying mode, and drying at a second temperature higher than the first temperature to obtain a pre-sintered material, wherein the chemical general formula of the substrate is Li[Ni 1‑x‑y Mn x Co y ]O2, x>0, y>0, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery cathode material technology, and in particular to a ternary cathode material and its preparation method. Background Technology

[0002] Currently, high-energy-density lithium nickel cobalt manganese oxide ternary cathode materials have become the preferred cathode material solution for the new energy vehicle industry due to their combined advantages of high specific capacity of lithium nickel oxide, good cycle performance of lithium cobalt oxide, and high safety of lithium manganese oxide. Ternary cathode materials have some performance defects, and one current improvement method is to coat them to reduce the contact area between the cathode material and the electrolyte, thereby reducing the occurrence of side reactions during long-term cycling, improving internal resistance, enhancing high-temperature cycle performance, and extending battery life. However, due to imperfections in the coating process, there is a loss of coating material during actual modification, resulting in a discrepancy between the actual coating amount and the design value, leading to less than ideal performance improvement. Summary of the Invention

[0003] The main technical problem addressed by this application is to provide a ternary cathode material and its preparation method, which can reduce the loss of coating material and reduce the gap between the actual coating amount and the design value.

[0004] To solve the above-mentioned technical problems, one technical solution adopted in this application is: to provide a method for preparing a ternary cathode material, comprising: The solvent, the first metal compound, and the second metal compound are mixed at a preset solid-liquid ratio to form a uniformly dispersed solid-liquid mixture system; the first metal compound is insoluble in the solvent, while the second metal compound is soluble in the solvent. The solid-liquid mixture is coated onto the surface of a substrate preheated to a first temperature using a high-pressure spray method, and then dried at a second temperature to obtain a pre-sintered material; the second temperature is higher than the first temperature, and the chemical formula of the substrate is Li[Ni]. 1-x-y Mn x Co y O2, x>0, y>0, 0 <x+y≤0.4; The pre-sintered material is sintered at a third temperature and then post-treated to obtain the ternary cathode material; the third temperature is higher than the second temperature.

[0005] Wherein, the first metal compound and the second metal compound contain at least one of the metal elements Zr, Al, Ti, Co, Sr, Mo, Y, Yb, Er, Ta, Sc, W, B, and Ba, and the mass ratio of the first metal compound to the second metal compound is (1-6):1.

[0006] Wherein, the parameter D50 characterizing the particle size of the first metal compound and the second metal compound is 50 nm to 5 μm.

[0007] Wherein, the solid-liquid ratio is 1:1 to 1:10.

[0008] Wherein, during the high-pressure spraying process, the coating ratio is 50 ppm to 20000 ppm, and the coating ratio is the ratio of the sum of the masses of the first metal compound and the second metal compound to the mass of the base material.

[0009] Wherein, the first temperature is 80°C to 200°C.

[0010] Wherein, after the base material is preheated to the first temperature, it is placed in a plowshare mixer for stirring and heat preservation, and both the high-pressure spraying and the drying performed at the second temperature are carried out in the plowshare mixer.

[0011] Wherein, the second temperature is 100°C to 300°C.

[0012] Wherein, the third temperature is 300°C to 800°C, and the sintering time is 6 h to 18 h.

[0013] To solve the above technical problems, one technical solution adopted by the present application is to provide a ternary positive electrode material, which is prepared by the preparation method described in the above technical solutions.

[0014] The beneficial effect of the present application is as follows: according to the preparation method of the ternary positive electrode material provided by the present application, firstly, a solvent, a first metal compound insoluble in the solvent and a second metal compound soluble in the solvent are mixed according to a preset solid-liquid ratio to form a uniformly dispersed solid-liquid mixed system; then the solid-liquid mixed system is coated on the surface of the base material preheated to the first temperature by means of high-pressure spraying, and dried at a second temperature higher than the first temperature to obtain a pre-sintered material, wherein the general chemical formula of the base material is Li[Ni 1-x-y Mn x Co y O₂, x>0, y>0, 0<x+y≤0.4; finally, the pre-sintered material is sintered at a third temperature higher than the second temperature, and post-treated to obtain the ternary positive electrode material. It can be seen that in the present application, the uniformly dispersed solid-liquid mixed system formed by the soluble and insoluble metal compounds is sprayed in one step to complete the coating, and meanwhile, by preheating the base material, the coating material is quickly dried to complete the coating, which can reduce the loss of the coating material caused by the long-time high-temperature drying process of the solvent, thereby narrowing the gap between the actual coating amount and the designed value, further reducing the adhesion and agglomeration of the coating material, reducing the segregation of the coating material caused by solid sedimentation, improving the uniformity of the coating layer, and thus improving the long-term cycle stability of the positive electrode material. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Among them: Figure 1 This is a schematic flowchart of one embodiment of the preparation method of the ternary cathode material of this application; Figure 2 This describes the morphology of the powder particles after spray coating in Example 1 of this application; Figure 3 This describes the powder particle morphology after high-temperature sintering in Example 1 of this application; Figure 4 These are initial DCR comparison charts for each embodiment and each comparative example; Figure 5 This is a comparison chart of the cycle capacity retention rates of various embodiments and comparative examples. Detailed Implementation

[0016] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0017] Please see Figure 1 , Figure 1 This is a schematic flowchart of one embodiment of the preparation method of the ternary cathode material of this application. The preparation method includes the following steps S11-S13.

[0018] Step S11: The solvent, the first metal compound, and the second metal compound are mixed at a preset solid-liquid ratio to form a uniformly dispersed solid-liquid mixture system; the first metal compound is insoluble in the solvent, and the second metal compound is soluble in the solvent.

[0019] First, the solvent (e.g., water, ethanol, etc.), the first metal compound, and the second metal compound are mixed at a preset solid-liquid ratio to form a uniformly dispersed solid-liquid mixture system. Stirring is maintained to ensure the dispersibility of the first and second metal compounds in the solvent. The first and second metal compounds contain at least one of the following metal elements: Zr, Al, Ti, Co, Sr, Mo, Y, Yb, Er, Ta, Sc, W, B, and Ba. The mass ratio of the first and second metal compounds is (1–6):1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, etc.

[0020] The first metal compound is insoluble in the solvent, such as ZrO2, TiO2, CoO, MgO, Al2O3, Y2O3, Yb2O3, Er2O3, WO3, etc., while the second metal compound is soluble in the solvent, such as Zr(SO4)2, TiCl4, Co(NO3)2, MgSO4, Al2(SO4)3, YCl3, YbCl3, ErCl3, Na2WO4, etc.

[0021] Preferably, the particle size of the first metal compound and the second metal compound is controlled to be between 50 nm and 5 μm with a D50.

[0022] The preferred solid-liquid ratio is 1:1 to 1:10, such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.

[0023] Step S12: The solid-liquid mixture is coated onto the surface of a substrate preheated to a first temperature using a high-pressure spray method, and then dried at a second temperature to obtain a pre-sintered material; the second temperature is higher than the first temperature, and the chemical formula of the substrate is Li[Ni]. 1-x-y Mn x Co y O2, x>0, y>0, 0 <x+y≤0.4。

[0024] After forming a uniformly dispersed solid-liquid mixture, it is coated onto the surface of the substrate by high-pressure spraying, and then dried while stirring to evaporate the solvent, so that the first metal compound and the second metal compound are uniformly coated on the particle surface of the substrate.

[0025] During high-pressure spraying, the coating ratio is 50ppm to 20000ppm, such as 50 ppm, 200 ppm, 800 ppm, 3000 ppm, 8000 ppm, 10000 ppm, 15000 ppm, 20000 ppm, etc. This coating ratio is the ratio of the sum of the masses of the first metal compound and the second metal compound to the mass of the substrate.

[0026] Before coating, the substrate is preheated to a first temperature, specifically 80℃ to 200℃, such as 80℃, 100℃, 120℃, 150℃, 160℃, 180℃, 200℃, etc. After coating, it is dried at a second temperature, specifically 100℃ to 300℃, such as 100℃, 150℃, 180℃, 200℃, 220℃, 250℃, 300℃, etc.

[0027] After the substrate is preheated to a first temperature, it is placed in a plow mixer for stirring and kept at the first temperature. Then, a high-pressure spraying device is used to spray the solid-liquid mixture onto the surface of the substrate kept at the first temperature, and it is dried directly in the plow mixer at a second temperature while being stirred, so as to uniformly coat the surface of the substrate particles with the coating material.

[0028] Step S13: The pre-sintered material is sintered at a third temperature and then post-treated to obtain a ternary cathode material; the third temperature is higher than the second temperature.

[0029] After drying to obtain the pre-sintered material, it is placed in a kiln for sintering. The third temperature is 300℃~800℃, such as 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, etc., and the sintering time is 6h~18h, such as 6h, 8h, 10h, 12h, 14h, 16h, 18h, etc., so as to form a stable metallurgically bonded surface coating layer on the surface of the substrate particles.

[0030] This embodiment utilizes a uniformly dispersed solid-liquid mixture system formed by soluble and insoluble metal compounds to complete the coating in one step via spraying. Simultaneously, by preheating the substrate, the coating material is dried rapidly to complete the coating. This reduces the loss of coating material caused by prolonged high-temperature drying of the solvent, thereby narrowing the gap between the actual coating amount and the design value. It also reduces the phenomenon of coating material adhesion and agglomeration, reduces coating material segregation caused by solid sedimentation, improves the uniformity of the coating layer, and is conducive to the formation of a stable metallurgically bonded surface coating layer, thereby improving the long-term cycle stability of the cathode material.

[0031] Based on the same inventive concept, this application also provides a ternary cathode material, which is prepared by the preparation method in the above embodiments. This embodiment has the same beneficial effects as the above embodiments, and will not be repeated here.

[0032] Based on the same inventive concept, this application also provides a lithium-ion battery, which includes the ternary positive electrode material in the above embodiments, and of course also includes negative electrode material, separator, electrolyte, etc. that can be obtained from the solutions disclosed in the prior art. This lithium-ion battery also has the same beneficial effects as the above embodiments, which will not be repeated here.

[0033] The performance improvement brought about by the technical solution provided in this application is illustrated below with specific embodiments and comparative examples.

[0034] The ternary cathode material prepared according to the following process is referred to as Example 1: Weigh a certain amount of LiNi 0.7 Co 0.05 Mn 0.25 O2 substrate was added to a plow mixer for stirring and preheated to a first temperature of 150°C. Simultaneously, 800 ppm of insoluble Al2O3 and 200 ppm of soluble Al2(SO4)3 were mixed with water at a solid-liquid ratio of 1:4 (total coating material weight to pure water weight). The mixture was mechanically stirred for 20 minutes to form a stable and uniformly dispersed solid-liquid mixture. The solid-liquid mixture was then uniformly sprayed onto the substrate surface using a centrifugal spray device. The second drying temperature was set to 200°C, and the drying time was 0.5 hours. After drying, a pre-sintered material was obtained. Finally, the pre-sintered material was placed in a muffle furnace for sintering at a third temperature of 700°C for 10 hours, ultimately producing the ternary cathode material of Example 1 with a uniform surface coating.

[0035] Example 2 differs from Example 1 in that the solid-liquid ratio of the total coating material weight to the pure water weight is 1:2.

[0036] Example 3 differs from Example 1 in that the drying time after high-pressure spraying is 1 hour.

[0037] Comparative Example 1 differs from Example 1 in that the coating material is only 1000 ppm of Al2O3.

[0038] Comparative Example 2 differs from Example 1 in that the coating material is only 1000 ppm of Al2(SO4)3.

[0039] The morphology of the ternary cathode material particles from Example 1 was observed using scanning electron microscopy before and after sintering, as follows: Figure 2 and Figure 3 As shown, it was found that the ternary cathode material of Example 1 had a uniform surface coating, a relatively smooth overall surface, and smooth surface particles after high-temperature sintering, with a relatively uniform coating layer distribution.

[0040] The ternary cathode materials of each embodiment and comparative example were directly used as cathode materials for lithium-ion batteries, with metallic lithium as the anode material. The assembled coin cells were tested within a voltage range of 3.0–4.4V. The test results of the initial discharge specific capacity are shown in Table 1, and the test results of the initial DCR obtained from the 5C / 0.5C low-temperature initial impedance test are shown in Table 2. Figure 4 The test results for the 45℃ 1C cycle 100 times test are shown below. Figure 5 .

[0041]

[0042] As can be seen from Table 1, the specific capacity of each embodiment and each comparative example is comparable in terms of initial discharge. However, the amount of coating material measured in each embodiment is significantly closer to the design value, indicating that the preparation method provided in this application can reduce the loss of coating material and narrow the gap between the actual coating amount and the design value.

[0043] from Figure 4 and Figure 5 It can be seen that the initial DCR and cycle performance of each embodiment are better than those of the comparative examples, indicating that the preparation method provided in this application forms a uniformly covered metal compound coating layer on the surface of the ternary cathode material, which improves the problem of capacity decay and DCR impedance performance deterioration of the cathode material during long-term high-temperature cycling.

[0044] The above description is merely an embodiment of this application and does not limit the patent scope of this application. Any equivalent structural or procedural transformations made using the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of this application.

Claims

1. A method for preparing a ternary cathode material, characterized in that, include: The solvent, the first metal compound, and the second metal compound are mixed at a preset solid-liquid ratio to form a uniformly dispersed solid-liquid mixture system. The first metal compound is insoluble in the solvent, while the second metal compound is soluble in the solvent; The solid-liquid mixture is coated onto the surface of a substrate preheated to a first temperature using a high-pressure spray method, and then dried at a second temperature to obtain a pre-sintered material; the second temperature is higher than the first temperature, and the chemical formula of the substrate is Li[Ni]. 1-x-y Mn x Co y O2, x>0, y>0, 0 <x+y≤0.4; The pre-sintered material is sintered at a third temperature and then post-treated to obtain the ternary cathode material; the third temperature is higher than the second temperature.

2. The preparation method according to claim 1, characterized in that, The first metal compound and the second metal compound contain at least one of the following metal elements: Zr, Al, Ti, Co, Sr, Mo, Y, Yb, Er, Ta, Sc, W, B, and Ba, and the mass ratio of the first metal compound to the second metal compound is (1-6):

1.

3. The preparation method according to claim 2, characterized in that, The particle size parameter D50 for the first and second metal compounds is 50 nm to 5 μm.

4. The preparation method according to claim 2, characterized in that, The solid-liquid ratio is 1:1 to 1:

10.

5. The preparation method according to claim 1, characterized in that, During the high-pressure spraying process, the coating ratio is 50ppm to 20000ppm, and the coating ratio is the ratio of the sum of the masses of the first metal compound and the second metal compound to the mass of the substrate.

6. The preparation method according to claim 5, characterized in that, The first temperature is 80℃~200℃.

7. The preparation method according to claim 5, characterized in that, After the substrate is preheated to the first temperature, it is placed in a plow mixer for stirring and heat preservation, and both the high-pressure spraying and the drying at the second temperature are carried out in the plow mixer.

8. The preparation method according to claim 7, characterized in that, The second temperature is 100℃~300℃.

9. The preparation method according to claim 1, characterized in that, The third temperature is 300℃~800℃, and the sintering time is 6h~18h.

10. A ternary cathode material, characterized in that, The ternary cathode material is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Coating method of lithium ion battery cathode material

    CN108767232A

  • Nickel-based positive electrode material of lithium secondary battery and preparation method of nickel-based positive electrode material

    CN114520319A